2014
DOI: 10.1007/s00018-014-1634-z
|View full text |Cite
|
Sign up to set email alerts
|

Transient dynamics of Aβ contribute to toxicity in Alzheimer’s disease

Abstract: The aggregation and deposition of the amyloid-β peptide (Aβ) in the brain has been linked with neuronal death, which progresses in the diagnostic and pathological signs of Alzheimer’s disease (AD). The transition of an unstructured monomeric peptide into self-assembled and more structured aggregates is the crucial conversion from what appears to be a harmless polypeptide into a malignant form that causes synaptotoxicity and neuronal cell death. Despite efforts to identify the toxic form of Aβ, the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 191 publications
(245 reference statements)
0
72
0
Order By: Relevance
“…In addition, given the high complexity of the fibrillation process, and considering the overall dynamics of the assembly and disassembly of toxic amyloid species, the possibility that toxicity is displayed by different conformers should not be disregarded. Moreover, it has also been suggested that the ongoing aggregation process, rather than a clearly defined aggregate, is responsible for amyloid toxicity (30,63).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the high complexity of the fibrillation process, and considering the overall dynamics of the assembly and disassembly of toxic amyloid species, the possibility that toxicity is displayed by different conformers should not be disregarded. Moreover, it has also been suggested that the ongoing aggregation process, rather than a clearly defined aggregate, is responsible for amyloid toxicity (30,63).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have supported that indanone moiety plays an important role in AChEs inhibition. 18 In addition to this, curcumin appeared as a potential Aβ aggregation inhibitor with potent antioxidant activity 19 and the piperazine scaffold is also used extensively to develop AChE inhibitors, neuroprotective as well as antioxidant molecules. 17 Thus, our designed molecules are endowed with necessary pharmacophoric features required for AChEs inhibition, Aβ aggregation inhibition, neuroprotective and antioxidant activity, which may warrant their multifunctional activity for AD.…”
Section: Fig 1 Chemical Structures Of Well Known Cholinesterase Inhimentioning
confidence: 99%
“…Aβ1‐42 aggregates more quickly and stably than Aβ1‐40. Aβ1‐42 polymerization is believed to occur in sequential phases: First Aβ monomers aggregate into soluble oligomers that then form insoluble oligomers, generating protofibrils and fibrils (Hubin et al ., 2014). Soluble Aβ1‐42 oligomers constitute the more toxic form of the peptide (Bolmont et al ., 2007; Nimmrich & Ebert, 2009; Guglielmotto et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%